Projet de formation et de développement des ressources humaines : Rapport annuel - Dialogue McGill (2009)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2009)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

Baseline Data Report 2008-2009 : Regional Profiles of Quebec's English-speaking Communities Selected 1996-2006 Census Findings - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2009)
The Baseline Data Report 2009 uses 2006 census information to provide Quebec’s Englishspeaking regional communities with a view of their current position with respect to selected health determinants and, where possible, change and continuity since the census findings of 1996. It is the first report in the series of Baseline Data Reports produced since 2004 to situate these communities in an evolving ten year trend.
Keywords: Official Language Minority Community (OLMC)

Dialogue : Better Communication for Better Care - Dialogue McGill (2009)

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2009)

Delivering Health and Social Services in English to English-speakers in the Capitale-Nationale Region (CNR) Revised Access Program: 2006-2009 : Translated and Edited Version - Jeffery Hale - Saint Brigid's (JHSB) (2008)
To comply with the latter, the Capitale-Nationale Region's Health and Social Services Network Development Agency (CNR Agency) launched a review of the health and social services offered in English to English speakers in the region.

Executive Summary of the Document "Delivering Health and Social services in English to English-speakers in the Capitale-Nationale Region (CNR) Revised Access Program: 2006-2009" - Jeffery Hale - Saint Brigid's (JHSB) (2008)
Between June and November 2006, the Agency Responsible for Health and Social Services in Québec's Capitale-Nationale region (or the CNR Agency) prepared a comprehensive Access Program report. This document details how health and social services are delivered in English to English speakers in the greater Quebec City region.

Questions and Answers about Access to Health and Social Services in English in the Capitale-Nationale Region (CNR) - Jeffery Hale - Saint Brigid's (JHSB) (2008)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2008)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

The Training and Retention of Health Professionals Project - Dialogue McGill (2008)

The Baseline Data Report 2007-2008 : Quebec's Social and Health Survey Information - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2008)
The Health and Social Services Networking and Partnership Initiative (HSSNPI) is a funding program of the Quebec Community Groups Network mandated by Health Canada as a measure of the Federal Action Plan for Official Language Communities. The HSSNPI aims to support the creation of durable links and joint action between English-speaking communities and Quebec’s health and social services system. The Baseline Data Report is a series produced by the Community Health and Social Services Network (CHSSN) to serve as a relevant and comprehensive knowledge base regarding the health status and vitality of Quebec’s English‐speaking population. The report is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders to develop strategies to improve the well‐being of their constituencies.
Keywords: Official Language Minority Community (OLMC)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2007)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

The Baseline Data Report 2006-2007 - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2007)
In 2002, the Community Health and Social Services Network (CHSSN) was a key Contributor to the report of the Consultative Committee for English‐speaking Minority Communities to the Federal Minister of Health.1 The Consultative Committee report proposed a five year Global Intervention Plan to support the English‐speaking communities’ efforts to improve access to health and social services in their language in Quebec. The Consultative Committee emphasized that improved access was intimately tied to the ability of English‐speaking communities to develop local networks and effective partnerships with public sector agencies. It was proposed that by maintaining and improving English‐language access to a full range of health and social services across diverse regional populations that these partnerships would help to promote better health outcomes and ensure the vitality of Quebec’s English‐speaking communities. The Committee underlined the need to pay special attention to the more isolated and demographically weak communities which face special challenges in providing health and social services in English to their respective populations.
Keywords: Official Language Minority Community (OLMC)

Project Report : Community Health and Social Services Network (CHSSN) : Community Radio : January 1 to March 31, 2007 - Howarth, Kelly; Kueber, Russell (Community Health and Social Services Network (CHSSN), 2007)
The findings and processes were to be documented and shared with the Lower North Shore (local radio station and regional English-speaking organization, COASTERs Association). In addition, consultation and support was to be given to both service providers to increase their capacity to better serve the English-speaking regions in the future.

Creating Sustainable Initiatives to Retain and Maintain Health and Social Services Professionals on the Lower North Shore - Lavallée, Marissa (Coasters Association, 2007)
The Coasters Association, in partnership with the Centre de Sant et de Services Sociaux de la Basse-C te-Nord (CSSSBCN), received a Training and Human Resources Development Project from McGill University, for seven weeks from February 13th to March 31st, 2006, Phase 1, under the Retention and Distance Professional and Community Support Program, to conduct a needs assessment on the issue of hiring and retaining English Professionals on the Lower North Shore. The objective of this needs assessment was to develop Phase II which is a two-year proposal that would lead to the improvement of hiring and retaining Health and Social Services Professionals on the Lower North Shore. The long term intended outcome is the increase in access to Health and Social Services for English speaking residents on the territory. Another objective of this needs assessment is to contact institutional and community-based objectives (i.e Education & Health and Social Services) it is hoped that these contacts will lead to partnerships that will help to address the hiring and retention of English-speaking Professionals on the Lower North Shore.

Language Training Program : Findings and recommendations of the lexicon evaluation committee - McLaughlin, Sky; Rogers, Jim (Lexicon Evaluation Committee, 2006)

Social Support Networks in Quebec's English-speaking Communities : Building Community Vitality Through Social Capital Strategies - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
This report arises in response to one of the objectives of the “We Can Act” project sponsored by the Community Health and Social Services Network (CHSSN). The CHSSN is a network of 60 community resources, associations, foundations, public institutions and other stakeholders dedicated to the development of partnerships in health and social services for English‐speaking communities in Quebec. The CHSSN promotes knowledge‐based community development as a means for communities to enhance their vitality and improve the health and well‐being of their members. Consistent with the population health approach, CHSSN sponsors projects and partnerships which address health determinants affecting the health status of communities as well as supportive strategies to attain a sustainable health and social service system.
Keywords: Official Language Minority Community (OLMC)

A Study of Women's Needs on the Lower North Shore - Keats, Shannon A. (Coasters Association, 2006)
The mission of the Coasters Association is to develop knowledge of the needs and expectations of the fourteen (14) communities on the Lower North Shore, and act in partnership with community leaders, organizations and stakeholders to design and deliver community strategies, programs and services which respond to the region’s development challenges. In keeping with their mission and providing an opportunity to better the situation of women on the Lower North Shore, a project entitled “A Study of the Needs of Women on the Lower North Shore”, was initiated. The project began on the September 12th, 2005 and ended on March 31st, 2006 (29 weeks). The key goal of the project was to get women involved and talk about the issues facing them and to identify opportunities and lasting solutions, as well as make women aware of the programs and services that are available on the coast, through partnerships with other organizations and to help these women make use of those programs. The purpose of the project was to research information through means of a questionnaire and by organizing focus groups to develop a needs assessment and to establish a coalition (for Phase 2 of the project) to improve the overall status of women on the Lower North Shore of Quebec.

Rapport de Données de Base 2005-2006 : Accés aux services de santé et aux services sociaux en anglais au Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
Keywords: Official Language Minority Community (OLMC)

The Baseline Data Report 2005-2006 : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
Keywords: Official Language Minority Community (OLMC)

Training and Human Resources Development Project : Measure 1 : Language training program - Dialogue McGill (2005)
The language training program presented is part of the Training and Human Resources Development Project that McGill University is to implement. This project is designed to ensure that English-speaking Quebecers obtain equitable access, in their language, to the range of health and social services offered to the entire population. The project has been elaborated against a backdrop of sociodemographic changes affecting Québec’s English-speaking communities, the adoption of new legislation modifying the organization of work, and the modernization of the health and social services system. It will be geared to clinical projects now being prepared pertaining to the organization of services. The project is an additional means of reviewing and implementing regional programs of access to health and social services in the English language, as stipulated by the Act respecting health services and social services.

Caring for elderly parents? Balancing family with work or studies? You may be part of the sandwich generation... - Howarth, Kelly (2005)

Brief on Building Local Health and Social Services Networks in Montreal - Allmand, Warren (English Speaking Catholic Council, 2004)
The ESCC was formed in 1980 as a focal point for coordinating community activities among English-speaking Roman Catholics in Montreal and later across all Quebec. In keeping with the mission of the Church and with its teachings on the role of the laity in the modern world, the English Speaking Catholic Council acts in the fields of education, health and social services, social justice and culture to build a sense of community identity and common purpose. We encourage the development of leadership in the community and assist in coordinating human resources in community-based institutions and we endeavour to ensure effective representation before government bodies and on various boards, committees and councils.

Mémoire du Conseil catholique d’expression anglaise sur la création de réseaux locaux de services de santé et de services sociaux à Montréal - Allmand, Warren (Conseil catholique d’expression anglaise, 2004)

Baseline Data Report 2003-2004 : Regional Profiles of English-speaking Communities - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2004)
This report includes a general overview of the situation of the English‐speaking population in a minority context as well as the particular demographic characteristics and vitality issues which vary tremendously across its 16 administrative health regions • The profile of each region is organized to highlight a broad range of factors that have been shown to have a strong influence on the health status of a population and ultimately the quality of life of its constituents • These health determinants are located in the context of national, provincial and regional demographic characteristics with comparisons between Anglophone minority and Francophone majority populations within a regional territory • Where significant, and possible, the tendencies of certain factors over time will be underlined • The commonalities among English‐speaking regional communities as well as the distinct features of each in terms of demographics, experiences, and attitudes are highlighted throughout this process and summarized in terms of key strengths and needs to be targeted in considering future health and social service initiatives
Keywords: Official Language Minority Community (OLMC)

Choices through Knowledge: Community training in palliative care - Jones, Jo-Ann; Quebec Association for Adult Learning (QAAL) (2004)

Population Health Initiative : A Community Guide to the Population Health Approach - Community Health and Social Services Network (CHSSN) (2003)

Alliance Quebec Will Take Action if PQ Reduces Guarentees of Access to English Health Services - Alliance Quebec (AQ) (2001)

AQ Requests Meeting with Premier Landry - Alliance Quebec (AQ) (2001)

Brief to the Estates General on the French Language - Alliance Quebec (AQ) (2001)
In 1982, following its long tradition of creating organizations and institutions to meet its needs and fulfill its aspirations, the English-speaking community created Alliance Quebec to respond to the dramatic changes in Quebec's society. Alliance Quebec is a non-profit, volunteer-based, community organization committed to the preservation and enhancement of the English-speaking communities and it's institutions in Quebec. Alliance Quebec serves as voice on public policy for the English-speaking communities. To that end, we strive for acceptance of an open and multicultural society; a commitment to a united Canada; a participative and integrated approach toward community retention and development; and proactive and entrepreneurial management.

Brief Presented to la commission des états généraux sur la situation et l'avenir de la langue française au Québec - The English Speaking Catholic Council (ESCC) (2001)
The English Speaking Catholic Council is a registered non-profit organization, made up of men and women from both the public and private sectors – all volunteers – who come together with a commitment to support and speak on behalf of their community in the fields of social justice, education, health and social services, and culture. In this year 2001, designated by the United Nations as the “International Year of Dialogue Among Civilizations”, the English Speaking Catholic Council comes before the Estates General with the hope of stimulating greater dialogue and understanding in a spirit of mutual respect among all people in Quebec.

Communication and Efficiency : Language and Health Care Brief Presented to the Clair Commission - Alliance Quebec (AQ) (2001)
Alliance Quebec welcomes the opportunity to present the concerns of the English-speaking community during the public consultations on the reorganization of health care. As we all know, communication is fundamental to proper diagnosis and treatment of the patient. It also plays a vital role in ensuring a patient is comfortable with his or her health care professional. Alliance Quebec is of the opinion that no matter how fine and efficient a health care system is, it will be less effective if it cannot communicate effectively with the patient and vice versa.

Mémoire à la Commission d'étude sur les services de santé et les services sociaux - Alliance Quebec (AQ) (2001)
Alliance Québec est heureuse d'avoir l'occasion d'exposer les préoccupations de la collectivité d'expression anglaise pendant les consultations publiques sur la réorganisation des soins de santé.

Making Quebec Health Care User-Friendly (Again) - Hamelin, Michael J.; Bechervaise, Lynden; Goodwin, Robina; King, Maurice; Buckle, Scott; May, Bob; Jackson, Léon (2001)

Nurses of Entry Island - Entry Island Historical Museum (2000)

The Ontario Government Should Fully Respect the Province's French-speaking Minority: AQ - Alliance Quebec (AQ) (2000)